DESIGN AND ANALYSIS OF A STATE OF CHARGE MONITORING SYSTEM FOR A SOLAR-WIND HYBRID SYSTEM USING THE COULOMB METHOD - Robby Mafirli; Dewi Anggraini; Tri Winahyu Hariyadi (AGUSPATI Research Institute, 2025)
This paper presents an analysis of the design and implementation of a state of charge (SOC) monitoring system for solar-wind hybrid systems using the Coulomb Count method. The purpose is to obtain real time measurements of voltage, current, temperature and SOC according to the battery management system. It is observed that when the 4.2 Ah battery is discharged, there is a significant drop in voltage and SOC, which is at a value of 45% to 40%, so that the cut-off voltage, namely the voltage required to avoid overcharging, is chosen at to avoid overcharging. It is chosen at 50% SOC and the voltage of 12 volts. When charging the 4.2 Ah battery, the voltage reached 16 volts at 75% SOC, with the battery temperature rising above 40°C, this value shows the importance of the cut-off voltage limit to avoid overcharging. Charging a 110 Ah battery with a solar/wind hybrid system using a PWM charger controller through the bulk, absorption and float phases shows that the bulk phase lasts about 18 minutes with an initial SOC of 47% and the absorption phase lasts 21 minutes and the last is the float phase where constant voltage and current occur for only 5 minutes. It is also found that the system can effectively follow the battery charge curve, preventing damage and ensuring the optimal condition of the charge controller.